THE EFFECT OF COMBINATION THERAPY OF STRAIGHT LEG RAISING EXERCISE AND RESISTED ACTIVE MOVEMENT ON PAIN RELIEF IN OSTEOARTHRITIS PATIENTS - husni; Tri Sella Anggraini; Mardiani (Nurse and Health: Jurnal Keperawatan, 2026)
Background: Osteoarthritis is a degenerative joint disease that frequently causes chronic pain, decreased mobility, and reduced quality of life. Non-pharmacological management through exercise therapy is recommended to reduce pain and improve joint function. Purpose: To determine the effect of a combination of Straight Leg Raising Exercise and Resisted Active Movement on pain intensity among osteoarthritis patients. Methods: This study used a quasi-experimental design with a pretest-posttest control group approach. A total of 60 respondents were selected using purposive sampling and divided into intervention and control groups, each consisting of 30 respondents. The intervention group received a combination of  Straight Leg Raising Exercise and Resisted Active Movement, while the control group received Range of Motion  exercises. Pain intensity was measured using the Numeric Rating  Scale . Data were analyzed using Wilcoxon and Mann-Whitney tests. Results: The average pain score in the intervention group decreased from 4.57 to 2.83, while in the control group it decreased from 4.43 to 3.23. Wilcoxon test showed significant differences before and after intervention in both groups  (p=0.000). Mann-Whitney test showed a significant difference in pain reduction between groups  (p=0.001). The median reduction in pain score was 2.00 in the intervention group and 1.00 in the control group. Conclusion: The combination of Straight Leg Raising Exercise and Resisted Active Movement significantly reduced pain intensity among osteoarthritis patients and was more effective than  Range of Motion exercises.